2019
DOI: 10.1111/jvh.13201
|View full text |Cite
|
Sign up to set email alerts
|

Use of cyclooxygenase inhibitor and the risk of hepatocellular carcinoma in patients with chronic hepatitis B: A nested case‐control study using a nationwide population‐based data

Abstract: The study aimed to investigate the relationship between the use of COX inhibitors and the risk of hepatocellular carcinoma (HCC) development in patients with chronic hepatitis B (CHB) using a nationwide population‐based data. A nested case‐control study was conducted using the National Health Insurance Service–National Sample Cohort (NHIS‐NSC) from 2002 to 2013 in Korea. We compared the use of COX inhibitors between HCC cases and matched controls by categorizing 5 groups according to the cumulative defined dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…The abnormal expression of cyclooxygenase in inflammation implies a potential chemoprevention target of HBV‐related HCC 85 . Research studies have shown an association between the reduced risk of HBV‐associated HCC and the use of a cyclooxygenase inhibitor, such as aspirin 86,87 . These results from clinical studies are consistent with previous findings that platelets facilitate immune‐mediated liver injury by promoting the hepatic accumulation of virus‐specific CD8(+) T cells 88 .…”
Section: The Role Of Therapeutic Interventions On Non‐viral Risk Factsupporting
confidence: 85%
“…The abnormal expression of cyclooxygenase in inflammation implies a potential chemoprevention target of HBV‐related HCC 85 . Research studies have shown an association between the reduced risk of HBV‐associated HCC and the use of a cyclooxygenase inhibitor, such as aspirin 86,87 . These results from clinical studies are consistent with previous findings that platelets facilitate immune‐mediated liver injury by promoting the hepatic accumulation of virus‐specific CD8(+) T cells 88 .…”
Section: The Role Of Therapeutic Interventions On Non‐viral Risk Factsupporting
confidence: 85%
“…Nine studies (n = 115 124) reported on HCC incidence. [28][29][30][31][32][33][34][35][36] The pooled aHR from seven matched cohort and case-control studies…”
Section: Hcc Incidencementioning
confidence: 99%
“…The case-control study by Cho et al 33 One three-arm study 36 (n = 840) evaluated the effects of APT and the matched results showed evidence that the use of aspirin or clopidogrel, alone or in combination, reduces the risk of HCC incidence; HR: 0.34, 95% CI: 0.15-0.7.…”
Section: Hcc Incidencementioning
confidence: 99%
See 2 more Smart Citations